Penerapan Metode Monte Carlo pada Simulasi Antrian Poliklinik RSUD DR. RM. Djoelham - Desty Dwi Putri; Akim M.H. Pardede; Anton Sihombing (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Long queues at the polyclinic of RSUD RM DR Djoelham Binjai often cause inconvenience to patients and reduce service efficiency. This study aims to analyze the queuing system at the hospital's polyclinic using the Monte Carlo method, which is able to model uncertainty in patient arrivals and service times. With this method, it is expected that a more accurate picture of patient waiting time and queue performance can be obtained so that improvement measures can be identified. The data used in this simulation includes the number of patients who come and the service time in the polyclinic. Monte Carlo simulations are carried out to predict various queuing scenarios based on variations that occur in patient arrivals and service duration. The simulation results provide information related to the estimated average waiting time of patients, and the level of queue density. This study shows that the application of the Monte Carlo method is effective in providing a more measurable solution to minimize waiting time and improve service quality at the polyclinic of RM DR Djoelham Binjai Hospital. These results are expected to be a reference for hospital management in making strategic decisions related to the optimization of health services. With the average waiting time for patients in the queue is 10.59 minutes while the average patient time is 25.34 minutes.